APPLICATION OF GAME METHODS TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' FOOTBALL PASSING LEARNING OUTCOMES - Sujarwo; Romdon, Rangga Aditia; Setiakarnawijaya, Yasep (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This research is in the form of action research to improve passing skills in soccer games among students at St. Cicilia I with a total of 54 students as subjects. This action research uses the Kemmis Taggart model which consists of two cycles. In this action research, playing methods are used to achieve the desired goals. Data was collected through observer observations in the form of passing skill tests, field notes, and documents during the research. The results of the research showed that after taking action using the playing method in cycle I, there were several students who were able to achieve a score exceeding the KKM. For the correctness test of the passing movement (process) in cycle I, only 19 (35%) students were declared complete, and only 19 (35%) students were declared 35 (65%) students did not complete it. Then, for the first cycle passing (product) accuracy test, only 26 (48%) students were declared complete, and 28 (52%) students were declared incomplete. From these results, there has been an increase, but as a group it has not exceeded 75% of the total number of students. Furthermore, in cycle II there was a significant increase. There were 46 (85%) students who were declared complete in the passing movement truth test (process), and 8 (15%) students who were declared incomplete. Then for the second cycle passing (product) accuracy test, 52 (96%) students were declared complete, and 2 (4%) students were declared incomplete. From the results of the second cycle passing skills test, it was declared complete because as a group, the percentage of students who achieved the minimum completeness criteria (KKM) score exceeded 75% of the total students, and it can be concluded that the application of the playing method can improve students' passing skills in soccer games SMP St. Cicilia I.